Analysis of Flow of Nozzles by Using Computational Fluid Dynamics - Lenin Rakesh, N.; Rambalaji, K. (International Journal of Psychosocial Rehabilitation, 2019)
Introduction Control of high-speed jets with passive control in the form of tabs of various shapes has been reported by large number of researchers in open literature. A tab is essentially a small solid strip kept normal to the flow, usually at the nozzle exit.